2011
DOI: 10.1128/aem.01361-10
|View full text |Cite
|
Sign up to set email alerts
|

Diversion of Flux toward Sesquiterpene Production in Saccharomyces cerevisiae by Fusion of Host and Heterologous Enzymes

Abstract: The ability to transfer metabolic pathways from the natural producer organisms to the well-characterized cell factory Saccharomyces cerevisiae is well documented. However, as many secondary metabolites are produced by collaborating enzymes assembled in complexes, metabolite production in yeast may be limited by the inability of the heterologous enzymes to collaborate with the native yeast enzymes. This may cause loss of intermediates by diffusion or degradation or due to conversion of the intermediate through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
162
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(172 citation statements)
references
References 37 publications
5
162
1
3
Order By: Relevance
“…4B, viii). It is unclear why it was possible to express ERG20 as a fusion with CFP and not as a fusion to the PcPs-YFP as has been described in yeast (Albertsen et al, 2011), however, this was not investigated further in this work. The relative productivity of patchoulol normalized to enzyme expression was indeed higher for the strains expressing the ispA-PcPs fusion.…”
Section: Precursor Fpp Synthase Fusion To Pcps Can Increase Patchoulomentioning
confidence: 62%
See 2 more Smart Citations
“…4B, viii). It is unclear why it was possible to express ERG20 as a fusion with CFP and not as a fusion to the PcPs-YFP as has been described in yeast (Albertsen et al, 2011), however, this was not investigated further in this work. The relative productivity of patchoulol normalized to enzyme expression was indeed higher for the strains expressing the ispA-PcPs fusion.…”
Section: Precursor Fpp Synthase Fusion To Pcps Can Increase Patchoulomentioning
confidence: 62%
“…It has been previously demonstrated that fusion of the yeast ERG20 FPPs to a PcPs resulted in higher titers of patchoulol production in the yeast host, with the assumption that close proximity of FPP substrate generation to the PcPs active site increases substrate channelling to the synthase (Albertsen et al, 2011). Since high titers of the PcPs synthase were desired for robust productivity, and the CrFPPs exhibited specialized localization in the cell, only ispA and ERG20 were chosen for fusion trials with the PcPs.…”
Section: Precursor Fpp Synthase Fusion To Pcps Can Increase Patchoulomentioning
confidence: 99%
See 1 more Smart Citation
“…Interaction domain Reference chimeric adapters protein [143] fusion enzymes protein [144] GBD-PDZ-SH3 scaffold protein [10] MAPK scaffold protein [145] two-component systemsp rotein [146] Thec lassical approach wase stablished due to historical developments as the first microorganisms were used as wild-type strains andt heir natural ability for production of certain chemicals was exploited. Fermentative production of ethanol by the yeast S. cerevisiae represents the most prominent example.…”
Section: Strategymentioning
confidence: 99%
“…Valencene, cubebol, patchoulol, and α-santalene are produced by expressing heterologous sesquiterpene synthase genes in S. cerevisiae [42][43][44][45][46][47]. Coexpression of the genes encoding valencene synthase gene and a P450 mono-oxygenase in S. cerevisiae generates nootkatone that is industrially produced as a flavoring agent and fragrance [48].…”
Section: Isoprenoidsmentioning
confidence: 99%